Sequential mechanisms underlying concentration invariance in biological olfaction - Cleland, Thomas A.; Chen, Szu-Yu T.; Hozer, Katarzyna W.; Ukatu, Hope N.; Wong, Kevin J.; Zheng, Fangfei (Frontiers in Neuroengineering, 2012)
Concentration invariance – the capacity to recognize a given odorant (analyte) across a range of concentrations – is an unusually difficult problem in the olfactory modality. Nevertheless, humans and other animals are able to recognize known odors across substantial concentration ranges, and this concentration invariance is a highly desirable property for artificial systems as well. Several properties of olfactory systems have been proposed to contribute to concentration invariance, but none of these alone can plausibly achieve full concentration invariance. We here propose that the mammalian olfactory system uses at least six computational mechanisms in series to reduce the concentration-dependent variance in odor representations to a level where different concentrations of odors evoke reasonably similar representations, while preserving variance arising from differences in odor quality. We suggest that the residual variance then is treated like any other source of stimulus variance, and categorized appropriately into “odors” via perceptual learning. We further show that naïve mice respond to different concentrations of an odorant just as if they were differences in quality, suggesting that, prior to odor categorization, the learning-independent compensatory mechanisms are limited in their capacity to achieve concentration invariance.